Integrating service learning into the curriculum: Lessons from the field. (12th January 2013) - Smith, Kirk L.; Meah, Yasmin; Reininger, Belinda; Farr, Miles; Zeidman, Jessica; Thomas, David C.
Abstract : The authors, representing two of the "signature" community service learning (CSL) programs in the 2010 Flexner Centenary volume of Academic Medicine, provide details of their programs – Frontera de Salud, a community-based program at the University of Texas Medical Branch, and the East Harlem Health Outreach Partnership, a clinic-based program at the Mount Sinai School of Medicine – specific to the task of integrating CSL into the medical school curriculum. They explain the nature and purpose of CSL, note gaps in the present curriculum which CSL aims to fill and highlight elements of CSL that are highly pertinent to Association of American Medical Colleges, Accreditation Council for Graduate Medical Education and Liaison Committee on Medical Education guidelines for undergraduate and graduate medical education. They also discuss barriers to the integration of CSL into the medical school curriculum and detail ways to overcome the logistic and fiscal challenges involved in making this highly effective and rewarding educational experience available to students of medicine.